Achievement Goal Orientations and Adolescents’ Subjective Well-Being in School: The Mediating Roles of Academic Social Comparison Directions - Tian, Lili; Yu, Tingting; Huebner, E. Scott (Frontiers in Psychology, 2017)
The purpose of this study was to examine the multiple mediational roles of academic social comparison directions (upward academic social comparison and downward academic social comparison) on the relationships between achievement goal orientations (i.e., mastery goals, performance-approach goals and performance-avoidance goals) and subjective well-being (SWB) in school (school satisfaction, school affect) in adolescent students in China. A total of 883 Chinese adolescent students (430 males; Mean age = 12.99) completed a multi-measure questionnaire. Structural equation modeling was used to examine the hypotheses. Results indicated that (1) mastery goal orientations and performance-approach goal orientations both showed a statistically significant, positive correlation with SWB in school whereas performance-avoidance goal orientations showed a statistically significant, negative correlation with SWB in school among adolescents; (2) upward academic social comparisons mediated the relation between the three types of achievement goal orientations (i.e., mastery goals, performance-approach goals and performance-avoidance goals) and SWB in school; (3) downward academic social comparisons mediated the relation between mastery goal orientations and SWB in school as well as the relation between performance-avoidance goal orientations and SWB in school. The findings suggest possible important cultural differences in the antecedents of SWB in school in adolescent students in China compared to adolescent students in Western nations.